Transformasi Peran Pesantren Sebagai Agen Sosial-Religius: Pertautan Tradisi dan Modernitas dalam Pemberdayaan Masyarakat di Madura - Abdullah, Abdullah; Muawaroh, Lailatul Mundiro (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2024)
This study examines the dual role of pesantren as a religious and social institution in society. To maintain their relevance, pesantren need to maintain valuable traditions while integrating modern methods, evaluations, and resources. This quantitative research discusses the framework of Socio-Religious Education, emphasizing the importance of forming individuals who have strong social awareness and behavior in accordance with Islamic teachings. Through the pesantren community development program, Socio-Religious Education makes a significant contribution to the empowerment of the people. These programs use persuasive, educative, participatory, and normative approaches in community development. The findings of the study show that the pesantren community development initiative does not follow the conventional economic growth paradigm, but rather emphasizes a participatory approach that is in line with the values of independence. This research is expected to contribute to the development of Islamic educational thought, especially related to the role of Islamic boarding schools in society, nation, and state